Drivers of pelagic and benthic microbial communities on Central Arctic seamounts - von Jackowski, Anabel; Walter, Maren; Spiegel, Timo; Buttigieg, Pier Luigi; Molari, Massimiliano (Frontiers in Marine Science, 2023)
Seamounts are abundant features on the seafloor that serve as hotspots and barriers for the dispersal of benthic organisms. The primary focus of seamount ecology has typically been on the composition and distribution of faunal communities, with far less attention given to microbial communities. Here, we investigated the microbial communities in the water column (0-3400 m depth) and sediments (619-3883 m depth, 0-16 cm below seafloor) along the ice-covered Arctic ridge system called the Langseth Ridge. We contextualized the microbial community composition with data on the benthic trophic state (i.e., organic matter, chlorophyll-a content, and porewater geochemistry) and substrate type (i.e., sponge mats, sediments, basaltic pebbles). Our results showed slow current velocities throughout the water column, a shift in the pelagic microbial community from a dominance of Bacteroidia in the 0-10 m depth towards Proteobacteria and Nitrososphaeria below the epipelagic zone. In general, the pelagic microbial communities showed a high degree of similarity between the Langseth Ridge seamounts to a northern reference site. The only notable differences were decreases in richness between 600 m and the bottom waters ( 10 m above the seafloor) that suggest a pelagic-benthic coupling mediated by filter feeding of sponges living on the seamount summits. On the seafloor, the sponge spicule mats, and polychaete worms were the principal source of variation in sedimentary biogeochemistry and the benthic microbial community structure. The porewater signature suggested that low organic matter degradation rates are accompanied by a microbial community typical of deep-sea oligotrophic environments, such as Proteobacteria, Acidimicrobiia, Dehalococcoidia, Nitrospira, and archaeal Nitrososphaeria. The combined analysis of biogeochemical parameters and the microbial community suggests that the sponges play a significant role for pelagic-benthic coupling and acted as ecosystem engineers on the seafloor of ice-covered seamounts in the oligotrophic central Arctic Ocean.